Drawing with hand, head, and heart a natural approach to learning the art of drawing - James, Van 1949- (SteinerBooks, 2015)
Part one: drawing for teachers of school-age children -- 1. Every children is an artist: the beginnings of drawing -- 2. Growing the picture: early drawing lessons in the primary school years (before age 10) -- 3. The changing child: drawing in the late elementary and middle school years (age 10 to teens) -- 4. A new perspective: drawing in the high school years -- Part two: drawing for students/artists of all ages -- Form drawing: a language of line and pattern -- The portrait: picturing oneself in the world -- Drawing as the art and science of seeing: from line, light and darkness to color